Comportamiento morfo-agroproductivo de diferentes cultivares de pimiento (capsicum anuum l.) en la parroquia la victoria - Sanchez Mosquera, Joe Vicente (Machala : Universidad Técnica de Machala, 2021)
Pepper is recognized as one of the most important vegetables for its high nutritional content and the good profitability it offers to the producer. The goodness of pepper (vitamin C, capsanthin, antioxidant pigments, provitamin A) has contributed to the development of research with important achievements in the development of new hybrids, with better production and resistance to unfavorable biological and physical conditions. The crop develops in different areas of the country, but its productivity is related to the adaptability of the different cultivars to the different climatic conditions, since to obtain high yields requires warm or temperate climates. This research work was carried out on the experimental farm of the Technical Agricultural College Eugenio Espejo located in the parish La Victoria belonging to the canton Las Lajas, with the purpose of demonstrating the morbid-agroproductive behavior of four pepper cultivars. To demonstrate the results in the different cultivars in morpho-agroproductive parameters it was necessary to apply the simple Latin square design with an area of 90.5 m2 with a total of 16 experimental units (4 treatments with 4 repetitions) of 4 m2 each experimental unit. To reduce the effect caused by uncontrolled factors such as soil moisture and fertilizing, experimental units were placed in columns and rows. Each cultivar corresponds to a treatment, the cultivars under study were Padrón, Cubanelle, Marconi and Yolo Wonder. The variables evaluated at 30, 45 and 60 days after transplantation were: fork height in the plant (cm), plant height (cm), number of leaves and stem diameter (mm). The days of flowering were taken at the time that 50% of the plants per experimental unit presented flowers and finally the number of fruits per plant, quantity of fruits harvested per plant in the first harvest, fruit diameter (mm), fruit length (cm), fruit weight (g) and agricultural yield (t ha-1)were measured at harvest time. A factorial ANOVA was applied to determine whether or not there are statistical differences between treatments based on the variables evaluated. Obtaining the results indicates that the cultivar Padrón (19.6 cm) and Marconi (19.4 cm) reached the highest height in their fork 30 days after transplantation presenting equality between them, but different statistically with the cultivars Cubanelle and Yolo Wonder. In the variable height of the plant the cultivar that presented the greatest value in the three moments of evaluation was the cultivar Padrón with an average height of 44.8 cm at 60 days after transplantation and the cultivar Yolo Wonder presented the value in the variable plant height. The Padron cultivar had the highest value in the number of active leaves during the three evaluation moments. The Cubanelle and Yolo Wonder cultivars presented equality between them with lower values in the stem diameter variable 60 days after transplantation, but statistically different with the Padrón and Marconi cultivars that showed greater diameter. As for the characteristics of the fruits, the cultivar Yolo Wonder had a larger diameter (58.7 mm) while the cultivar Padron showed the smallest diameter (35.26 mm). In the length of the fruit the cultivar Marconi (13.2 cm) presented a greater value while the cultivars Padrón and Yolo Wonder showed equality between them, but with lower value means. The cultivar Padrón (5 fruits) obtained greater value in number of fruits per plant, the cultivars Cubanelle (3 fruits) and Marconi (3 fruits) obtained intermediate values presenting equality between them, while the cultivar Yolo Wonder (2 fruits) presented the lowest value. In the fruit weight variable the cultivar Yolo Wonder (68.7 g) had higher value, different statistically from other treatments, while Padrón (22.6 g) had the lowest fruit weight. The variables that allowed to establish agricultural yield were: plant height, number of fruits per plant, length, diameter and weight of the fruit placing when growing Cubanelle with better agricultural yield (2.12 t ha-1) in the locality, also presented precocity in flowering and greater curdling of the fruits which can be an indicator of the adaptation of this cultivar to the edaphoclimatic conditions and management of the crop in the area.
El pimiento es reconocido como una de las hortalizas más importantes por su alto contenido nutricional y la buena rentabilidad que ofrece al productor. Las bondades del pimiento (vitamina C, capsantina, pigmentos antioxidantes, provitamina A) han contribuido al desarrollo de investigaciones con logros importantes en el desarrollo de nuevos híbridos, con mejor producción y resistencia a condiciones biológicas y físicas desfavorables. El cultivo se desarrolla en diferentes zonas del país, pero su productividad se encuentra relacionada con la adaptabilidad de los diferentes cultivares a las distintas condiciones climáticas, ya que para obtener altos rendimientos requiere de climas cálidos o templados. El presente trabajo investigativo se realizó en la granja experimental del Colegio Técnico Agropecuario Eugenio Espejo ubicado en la parroquia La Victoria perteneciente al cantón Las Lajas, con el propósito de demostrar el comportamiento morfo-agroproductivo de cuatro cultivares de pimiento. Para evidenciar los resultados en los diferentes cultivares en parámetros morfo-agroproductivos fue necesario la aplicación del diseño cuadrado latino simple con un área de 90.5 m2 con un total de 16 unidades experimentales (4 tratamientos con 4 repeticiones) de 4 m2 cada unidad experimental. Para reducir el efecto provocado por factores no controlados como la humedad del suelo y la fertilizad se ubicó las unidades experimentales en columnas e hileras. Cada cultivar corresponde a un tratamiento, los cultivares objeto de estudio fueron Padrón, Cubanelle, Marconi y Yolo Wonder. Las variables evaluadas a los 30, 45 y 60 días después del trasplante fueron: altura de la bifurcación en la planta (cm), altura de la planta (cm), número de hojas y diámetro del tallo (mm). Los días a la floración se tomó en el momento que el 50% de las plantas por unidad experimental presentaron flores y finalmente el número de frutos por planta, cantidad de frutos recolectados por planta en la primera cosecha, diámetro del fruto (mm), longitud del fruto (cm), peso del fruto (g) y rendimiento agrícola (t ha-1) fueron medidos en el momento de la cosecha. Se aplicó un ANOVA factorial intersujetos para determinar si existen o no diferencias estadísticas entre los tratamientos en función a las variables evaluadas. Mediante la obtención de los resultados se indica que el cultivar Padrón (19.6 cm) y Marconi (19.4 cm) alcanzaron la mayor altura en su bifurcación a los 30 días después del trasplante presentando igualdad entre ellos, pero diferentes estadísticamente con los cultivares Cubanelle y Yolo Wonder. En la variable altura de la planta el cultivar que presentó el mayor valor en los tres momentos de evaluación fue el cultivar Padrón con una altura media de 44.8 cm a los 60 días después del trasplante y el cultivar Yolo Wonder presentó el menor valor en la variable altura de planta. El cultivar Padrón presentó el mayor valor en el número de hojas activas durante los tres momentos de evaluación. Los cultivares Cubanelle y Yolo Wonder presentaron igualdad entre ellos con valores menores en la variable diámetro del tallo a los 60 días después del trasplante, pero diferentes estadísticamente con los cultivares Padrón y Marconi que mostraron mayor diámetro. En cuanto a las características de los frutos el cultivar Yolo Wonder presentó mayor diámetro (58.7 mm) mientras que el cultivar Padrón mostró el menor diámetro (35.26 mm). En la longitud del fruto el cultivar Marconi (13.2 cm) presentó un mayor valor mientras que los cultivares Padrón y Yolo Wonder mostraron igualdad entre ellos, pero con medias de menor valor. El cultivar Padrón (5 frutos) obtuvo mayor valor en número de frutos por planta, los cultivares Cubanelle (3 frutos) y Marconi (3 frutos) obtuvieron valores intermedios presentando igualdad entre ellos, mientras que el cultivar Yolo Wonder (2 frutos) presentó el menor de valor. En la variable peso del fruto el cultivar Yolo Wonder (68.7 g) presentó mayor valor, diferente estadísticamente al resto de tratamientos, mientras que Padrón (22.6 g) presentó el menor peso de fruto. Las variables que permitieron establecer el rendimiento agrícola fueron: altura de planta, número de frutos por planta, longitud, diámetro y peso del fruto colocando al cultivar Cubanelle con mejor rendimiento agrícola (2.12 t ha-1) en la localidad, además presentó precocidad en la floración y mayor cuajado de los frutos lo que puede constituir un indicador de la adaptación de este cultivar a las condiciones edafoclimáticas y de manejo del cultivo en la zona.
Keywords: PIMIENTO; CULTIVAR; RENDIMIENTO; PARÁMETROS